The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1017/s0007114522000757
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of malaria infection on indicators of iron and vitamin A status: a systematic literature review and meta-analysis

Abstract: Inflammation and infections such as malaria affect estimates of micronutrient status. Medline, Embase, Web of Science, Scopus and the Cochrane library were searched to identify studies reporting mean concentrations of ferritin, hepcidin, retinol or retinol binding protein in individuals with asymptomatic or clinical malaria and healthy controls. Study quality was assessed using the United States National Institute of Health tool. Random-effects meta-analyses were used to generate summary mean differences. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
(174 reference statements)
0
10
0
Order By: Relevance
“… 60 Therefore, biomarkers of iron and vitamin A status should be statistically adjusted for malaria and the severity of infection. 61 Most of the included studies in our systematic review were done in malaria-endemic areas; however, none reported adjustments for malaria. Thus, the effect of malaria on our results cannot be accurately judged.…”
Section: Discussionmentioning
confidence: 99%
“… 60 Therefore, biomarkers of iron and vitamin A status should be statistically adjusted for malaria and the severity of infection. 61 Most of the included studies in our systematic review were done in malaria-endemic areas; however, none reported adjustments for malaria. Thus, the effect of malaria on our results cannot be accurately judged.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the role of inflammation in assessing micronutrient status is essential to interpret micronutrient deficiencies correctly [14]. The BRINDA method has been used in various studies and national surveys [23][24][25] and included in WHO ferritin guidelines [14] and CDC's Micronutrient Manual and Toolkit [15]. The evidence gained from the BRINDA project has provided important insights to research, policy, and programming [26].…”
Section: Discussionmentioning
confidence: 99%
“…The role of malaria as a binary variable does not affect the results of BRINDA inflammation adjustment on a series of micronutrient biomarkers, namely, ferritin, sTfR, retinol, RBP, and zinc, using the latest BRINDA database. However, the stage of malaria infection may influence the results for the BRINDA inflammation adjustment method [ 24 ] and warrants more consideration in the future. Although the BRINDA inflammation adjustment method has not been applied within clinical settings, research on its utility in this setting is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Iron homeostasis is dependent on a complex interplay of physiological mediators 1,2 and is highly sensitive to inflammatory diseases, such as malaria (e.g. Plasmodium falciparum malaria) 3 . Severe malaria disease is frequently accompanied by anaemia due to haemolysis of parasitized erythrocytes 4 .…”
Section: Characteristic Controls Cases P‐value Aparasitaemic N = 209 ...mentioning
confidence: 99%
“…Plasmodium falciparum malaria). 3 Severe malaria disease is frequently accompanied by anaemia due to haemolysis of parasitized erythrocytes. 4 In the acute situation, this contributes to the disease burden since tissue oxygenation and energy metabolism are impaired.…”
mentioning
confidence: 99%